Compressive Strength Analysis of Renewable Mortar after Portland Cement Replacement with Waste Ash - Syarif, Muhammad; Nanda, Abdul Rakhim; Nurnawaty, .; Imran, Hamzah Al; Karim, Nenny; Yusri, Andi (Engineering, Technology & Applied Science Research, 2024)
There are many environmental problems caused by factory waste. Sugar factory waste, in the form of bagasse ash, and PLTU factory waste, in the form of fly ash, are currently in the spotlight of science studies. This study used waste bagasse and fly ash to substitute Portland cement as the main ingredients for mortar. Baggash and fly ash waste were collected, processed, and then used to replace cement by up to 40% to determine to what extent they could be used in brick masonry work, wall plastering, and masonry paste. Experimental tests were carried out on mortar cube samples measuring 5×5×5 cm, comparing four types of samples consisting of Portland cement, bagasse ash, and fly ash. The compressive strength results were obtained after 28 days. Normal Mortar (MN=11.75 MPa) had higher compressive strength than the substitute mortar types MA (3.23 MPa), MB (3.09 MPa), and MC (2.98) MPa. According to SNI 6882-2014, MA, MB, and MC mortars can be used as O-type mortar (2.4 MPa). Therefore, they can be applied to wall plastering or walls not bearing loads.